2013
DOI: 10.1111/j.1365-4632.2012.05759.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous tuberculosis of the pinna: a report of two cases

Abstract: Lupus vulgaris is the most common form of cutaneous TB. It is important to diagnose LV because it can result in chronic disfigurement and because 10-20% of LV patients have active pulmonary TB or TB of the bones and joints. In addition, longstanding LV is known to lead to the development of squamous cell carcinoma, which can be avoided by early diagnosis and treatment with ATT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 9 publications
0
17
1
2
Order By: Relevance
“…In another study, Semaan R. et al reported the case of two immunocompetent patients who presented primary cutaneous tuberculosis [6]. In a study by Kaimal et al [7], two cases of Lupus vulgaris with the exclusive involvement of the ear lobe have been reported in immunocompetent women and neither had a personal or family history of TB. In India, the incidence of cutaneous tuberculosis has fallen from 2% to 0.15% [8].…”
Section: Discussionmentioning
confidence: 96%
“…In another study, Semaan R. et al reported the case of two immunocompetent patients who presented primary cutaneous tuberculosis [6]. In a study by Kaimal et al [7], two cases of Lupus vulgaris with the exclusive involvement of the ear lobe have been reported in immunocompetent women and neither had a personal or family history of TB. In India, the incidence of cutaneous tuberculosis has fallen from 2% to 0.15% [8].…”
Section: Discussionmentioning
confidence: 96%
“…Lupus vulgaris occurring at atypical sites often leads to delayed diagnosis, inappropriate treatment, and significant long‐term sequelae such as scarring and mutilation. Face is less commonly affected in the Indian population, with the nose and cheeks reported as the sites of predilection . Ear lobe as the primary site of involvement is uncommon in lupus vulgaris and is usually unilateral in presentation .…”
Section: Discussionmentioning
confidence: 99%
“…Face is less commonly affected in the Indian population, with the nose and cheeks reported as the sites of predilection . Ear lobe as the primary site of involvement is uncommon in lupus vulgaris and is usually unilateral in presentation . Kaimal et al reported two patients who had eczematous and ulcerated plaques with purulent discharge involving the pinna and ear lobe on one side .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multidrug resistance and HIV infection are predisposing factors for the disease, since the immune response of the patient plays a significant role on clinical manifestation of tuberculosis [10-12]. Extrapulmonary tuberculosis accounts for 13% of all cases [4].…”
Section: Discussionmentioning
confidence: 99%